Microglial Intracellular Ca2+ Signaling in Synaptic Development and its Alterations in Neurodevelopmental Disorders - Mizoguchi, Yoshito; Monji, Akira (Frontiers in Cellular Neuroscience, 2017)
Autism spectrum disorders (ASDs) are neurodevelopmental disorders characterized by deficits in social interaction, difficulties with language, and repetitive/restricted behaviors. Microglia are resident innate immune cells which release many factors including proinflammatory cytokines, nitric oxide (NO) and brain-derived neurotrophic factor (BDNF) when they are activated in response to immunological stimuli. Recent in vivo imaging has shown that microglia sculpt and refine the synaptic circuitry by removing excess and unwanted synapses and be involved in the development of neural circuits or synaptic plasticity thereby maintaining the brain homeostasis. BDNF, one of the neurotrophins, has various important roles in cell survival, neurite outgrowth, neuronal differentiation, synaptic plasticity and the maintenance of neural circuits in the CNS. Intracellular Ca2+ signaling is important for microglial functions including ramification, de-ramification, migration, phagocytosis, and release of cytokines, NO and BDNF. BDNF induces a sustained intracellular Ca2+ elevation through the upregulation of the surface expression of canonical transient receptor potential 3 (TRPC3) channels in rodent microglia. BDNF might have an anti-inflammatory effect through the inhibition of microglial activation and TRPC3 could play important roles in not only inflammatory processes but also formation of synapse through the modulation of microglial phagocytic activity in the brain. This review article summarizes recent findings on emerging dual, inflammatory and non-inflammatory, roles of microglia in the brain and reinforces the importance of intracellular Ca2+ signaling for microglial functions in both normal neurodevelopment and their potential contributing to neurodevelopmental disorders such as ASDs.